2004
DOI: 10.1590/s1413-86702004000300011
|View full text |Cite
|
Sign up to set email alerts
|

Human ehrlichioses in Brazil: first suspect cases

Abstract: Brazilian spotted fever (BSF) rickettsiosis is the most common and recognized of the human rickettsioses in Brazil. It is difficult to establish the diagnosis of human rickettsiosis infection by routine microbiologic methods, creating a false idea that Rickettsia and Ehrlichia infections are rare and without importance. New tick-borne diseases, like human granulocytic anaplasmosis (HGA) and human monocytic ehrlichiosis (HME), have been described in many countries. These diseases can present symptoms similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 8 publications
1
30
0
13
Order By: Relevance
“…Also, the present work showed for the first time the detection of E. chaffeensis in a carnivorous bird. While knowledge about the epidemiology of this zoonotic agent in Brazil lies in its molecular detection in Brazilian marsh deer (Machado et al 2006), and serological detection among dogs and humans (Calic et al 2004;Costa et al 2005), our study highlights the participation of birds in the dispersal of this pathogen, and the possibility of the establishment of new foci of infection among animals and humans. In Slovakia, an Ehrlichia-like species ''Schotti variant'' was detected in a nymph from the song thrush (Turdus philomelos) (Spitalská et al 2006).…”
Section: Anaplasmataceae In Wild Birds In Brazil 707mentioning
confidence: 80%
See 1 more Smart Citation
“…Also, the present work showed for the first time the detection of E. chaffeensis in a carnivorous bird. While knowledge about the epidemiology of this zoonotic agent in Brazil lies in its molecular detection in Brazilian marsh deer (Machado et al 2006), and serological detection among dogs and humans (Calic et al 2004;Costa et al 2005), our study highlights the participation of birds in the dispersal of this pathogen, and the possibility of the establishment of new foci of infection among animals and humans. In Slovakia, an Ehrlichia-like species ''Schotti variant'' was detected in a nymph from the song thrush (Turdus philomelos) (Spitalská et al 2006).…”
Section: Anaplasmataceae In Wild Birds In Brazil 707mentioning
confidence: 80%
“…In Brazil, Ehrlichia chaffeensis and Anaplasma phagocytophilum have been detected in Brazilian marsh deer (Blastocerus dichotomus) (Machado et al 2006) and dogs (Santos et al 2011), respectively. Regarding the occurrence of ehrlichiosis among humans in Brazil, only serological studies have been reported (Calic et al 2004;Costa et al 2005). Among wildlife in Brazil, Ehrlichia spp.…”
mentioning
confidence: 99%
“…Missing information regarding E. chaffeensis infections seems to the rule in Brazil where the first suspected human cases were just recently published by Calic et al (2004). Additional human cases were also described thereafter (Costa 2004) but the only previously published serosurvey carried out in Brazil on E. chaffeensis infection found null seroprevalence among humans but not in dogs from that very same region .…”
Section: Discussionmentioning
confidence: 99%
“…In South America a few cases of human erlichiosis are described due to E. canis and E. chaffeensis in Venezuela (PEREZ et al, 2006); and serologic evidence of human erlichiosis is found in Chile and Argentina (RIPOLL et al, 1999;LÓPEZ et al, 2003). In Brazil, suspected cases of human were demonstrated with clinical and laboratory findings and with positive serology for human granulocytic anaplasmosis (HGA) by Calic et al (2004). However, Brazilian spotted fever (BSF) is the most common form of human Rickettsia infection in our country.…”
Section: Introductionmentioning
confidence: 99%